Comparison of densification kinetics of a TiAl powder by spark plasma sintering and hot pressing. (15th August 2017) - Trzaska, Zofia; Bonnefont, Guillaume; Fantozzi, Gilbert; Monchoux, Jean-Philippe
Abstract: Densification kinetics by spark plasma sintering (SPS) and hot pressing (HP) have been compared, under isothermal conditions and with heating rates of 20 °C/min. Careful calibration of sample temperature has been carried out to obtain comparable results. In all cases, densification kinetics did not exhibit significant differences, ruling out any influence of the SPS current. The stress exponent n and the activation energy Q of the Norton law describing deformation at high temperature of the powder particles have been determined by isothermal experiments at different stresses and temperatures, respectively. The values obtained, n  = 1.9 ± 0.3 and Q  = 308 ± 20 kJ/mol for SPS, n  = 1.5 ± 0.3 and Q  = 276 ± 40 kJ/mol for HP, come close in both techniques. Using these values, anisothermal densification kinetics at heating rates of 20°C/min and 100 °C/min, typical of the SPS, could be analytically reproduced, using literature models. The activation parameters suggest that SPS densification kinetics occurs by dislocation climb controlled by Al bulk diffusion, that is, by classical metallurgical mechanisms. Graphical abstract: Image